Synthesis of some tetrahydropyrimidine-5-carboxylates, determination of their metal chelating effects and inhibition profiles against acetylcholinesterase, butyrylcholinesterase and carbonic anhydrase - Sujayev, Afsun; Garibov, Emin; Taslimi, Parham; Gülçin, İlhami; Gojayeva, Sevinj; Farzaliyev, Vagif; Alwasel, Saleh H.; Supuran, Claudiu T.; Taslimi, Parham (Informa, 2016)
2-(Methacryloyloxy)ethyl 6-methyl-2-oxo-4-phenyl-1,2,3,4-tetrahydropyrimidine-5-carboxylate, is a cyclic urea derivative synthesized from urea, 2-(methacryloyloxy) ethyl acetoacetate and substituted benzaldehyde, and tested in terms of the inhibition of two physiologically relevant carbonic anhydrase (CA) isozymes I and II. Acetylcholinesterase (AChE) is found in high concentrations in the red blood cells and brain. Butyrylcholinesterase (BChE) is another enzyme abundantly present in the liver and released into blood in a soluble form. Also, they were tested for the inhibition of AChE and BChE enzymes and demonstrated effective inhibition profiles with Ki values in the range of 429.24-530.80 nM against hCA I, 391.86-530.80 nM against hCA II, 68.48-97.19nM against AChE and 104.70-214.15 nM against BChE. On the other hand, acetazolamide clinically used as CA inhibitor, showed Ki value of 281.33 nM against hCA I, and 202.70 nM against hCA II. Also, Tacrine inhibited AChE and BChE showed Ki values of 396.03 and 209.21 nM, respectively.
Keywords: Acetylcholinesterase; X-ray; Butyrylcholinesterase; Carbonic anhydrase; Urea